Clinical evaluation of corono-radicular restorative design with fibre post restoration for fractured endodontically treated maxillary incisors: A randomised control trial - M R Pradeepa; I Anand Sherwood; Bennett Tochukwu Amaechi; S Swathi Priyadharshini; A Azhagu Abirami (Wolters Kluwer Medknow Publications, 2023)
Aim: The primary aim was to evaluate and compare the survivability of corono-radicular direct composite (CRDC) restoration and fiber-reinforced composite post (FRC) followed by coronal restoration for fractured root canal-treated maxillary incisors with a tooth structure loss of 50%-70%. Methods: A total of 56 teeth from 49 patients with fractured maxillary central and/or lateral incisors due to trauma were recruited for the study. The teeth were randomly allocated to two groups randomly by lot method. The two treatment groups were as follows: Group I - CRDC and Group II - FRC followed by coronal restoration. The postoperative review was performed at 3-, 12-, 18-, and 24-month period using intraoral periapical radiographs and clinical photographs. The Patient Satisfaction Questionnaire was administered during 24-month review visit. Kaplan-Meier survival analysis was used to assess the longevity of the restorations. Results: There was no significant difference (P > 0.05) in the survivability of the restorations among the two treatment groups. The mean survival period for CRDC was 24 months and FRC followed by coronal restoration was 23.74 months. The patient's satisfaction assessed using the questionnaire was higher in CRDC (100%) than FRC followed by coronal restoration (81.5%). Conclusion: Within the limit of the present study, both CRDC and FRC followed by coronal restoration were equally effective in the management of fractured maxillary incisors with 50%-70% tooth structure loss.